The last of the Mohicans - Cooper, James Fenimore; Sibley, Raymond; Humphris, Frank (Loughborough : Ladybird, 1997)
A tale of adventure, treachery, and friendship in the battle-torn wilderness of eighteenth-century upstate New York.
Keywords: Mohegan Indians -- Fiction; Action and adventure fiction